2006
DOI: 10.1136/hrt.2005.072314
|View full text |Cite
|
Sign up to set email alerts
|

Response to bosentan in children with pulmonary hypertension

Abstract: Objective: To describe an early experience of treating 40 children with the dual endothelin receptor antagonist bosentan, which is known to be safe and effective in adults with pulmonary hypertension (PH). Design: In this retrospective, observational study the UK Service for Pulmonary Hypertension for children treated 40 children with bosentan, 20 with idiopathic pulmonary arterial hypertension (IPAH) (mean age 8.03 years, range 1.2-17) and 20 with PH associated with other conditions (congenital heart disease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 26 publications
6
85
2
3
Order By: Relevance
“…Other less well-powered, open-label studies in smaller numbers of patients, often cases series or retrospective studies, have reported on the use of bosentan in paediatric patients with PAH [20][21][22][23][24]. In a study specifically carried out in PAH patients with systemic-to-pulmonary shunt, bosentan therapy produced short-term improvement (4 months) with respect to WHO functional class and 6-min walking distance both in 10 children and 25 adults [25].…”
Section: Bosentanmentioning
confidence: 99%
“…Other less well-powered, open-label studies in smaller numbers of patients, often cases series or retrospective studies, have reported on the use of bosentan in paediatric patients with PAH [20][21][22][23][24]. In a study specifically carried out in PAH patients with systemic-to-pulmonary shunt, bosentan therapy produced short-term improvement (4 months) with respect to WHO functional class and 6-min walking distance both in 10 children and 25 adults [25].…”
Section: Bosentanmentioning
confidence: 99%
“…Nonselektif ETA/ETB antagonisti olarak kullanılan bosentan kronik PHT tedavisinde tercih edilmektedir. OPAB ve PDD'ni azalttığı ve idiopatik PHT hastalarında yaşam kalitesini arttırdığı gösterilmiştir (17,18) . Eisenmenger sendromunda oksijen satürasyonunu azaltmadan egzersiz kapasitesini düzelttiği gösterilmiştir (19) .…”
Section: Endotelin Antagonistleri (Et-1)unclassified
“…Furthermore, it has been shown that bosentan ameliorates decreased skin perfusion and digital ulceration secondary to SSc [5,6]. A previous report showed that bosentan was effective for treatment of children with primary and secondary PAH [3]. However, the effectiveness and safety of bosentan for treatment of juvenile SSc still remains unclear.…”
Section: Introductionmentioning
confidence: 99%